Sensorineural Hearing Loss as a Filter in Word Comprehension - Mildner, Vesna (Array, 1999)
The purpose of the study was to examine how subjects with sensorineural hearing loss comprehend isolated words with respect to necessary intensity re their pure-tone and speech audiometry thresholds as well as with respect to sound content of the presented words. The study involved 12 subjects (mean age 77 years) with sensorineural hearing loss ranging between 40 and 77 dB in both ears, and pure-tone audiometry curves sloping down toward higher frequencies. The tests were performed using the pure-tone and speech audiometry apparatus and material. The subjects reached maximum intelligibility (sample mean 94%) on the average 31 dB above the threshold of hearing in speech audiometry. With respect to sound content of the presented words it was found that words consisting of predominantly low sounds whose characteristic frequencies are up to about 1 kHz (klupa) were repeated with the 57.35% accuracy; mid-frequency words, containing sounds whose chaacteristic frequencies are between 1 and 3.2 kHz (jaje), were repeated with 60.86% accuracy, and high words, containing sounds whose characteristic frequencies are above 3.2 kHz (zmija), were repeated least correctly (54.28% accuracy).